Kebijakan Hilirisasi Kopi Di Indonesia: Implementasinya Di Tingkat Lokal - Cordanis, Astried Priscilla; Hutagaol, Manuntun Parulian; Harianto, Harianto (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2025)
Coffee downstreaming in Indonesia is supported by the government based on various policies that encourage aspects of production, productivity, and competitiveness in an effort to improve export quality. The downstreaming policy in Indonesia provides opportunities for the coffee industry in Indonesia to increase competitiveness in both the domestic and international markets. Indirectly, this policy is also expected to improve the welfare of farmers at the local level. Therefore, the purpose of this article is to determine whether the coffee downstreaming policy can improve coffee farmers at the local level, as well as policy recommendations in improving the welfare of these coffee farmers. The method used in answering the objectives of this article uses literature studies related to coffee production, downstreaming policies, added value, value chains, coffee competitiveness, and related agricultural policies explained using the Tinbergen framework approach. It was found that the coffee downstreaming policy did not have a direct impact on farmers, but rather on the coffee processing industry in Indonesia. The fairly long supply chain causes the downstreaming policy to have an indirect impact on farmers. The success of this downstreaming policy requires synergy between agricultural stakeholders in improving farmer welfare, namely: central and regional governments, industry, traders, financial institutions, cooperatives and farmer associations. The success of this policy is an increase in productivity, an increase in product quality, and wider market access.